2009
DOI: 10.1161/circep.109.882910
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Septal and Left Ventricular Apical Pacing Chronically Maintain Cardiac Contractile Coordination, Pump Function and Efficiency

Abstract: Background-Conventional right ventricular (RV) apex pacing can lead to adverse clinical outcome associated with asynchronous activation and reduced left ventricular (LV) pump function. We investigated to what extent alternate RV (septum) and LV (septum, apex) pacing sites improve LV electric activation, mechanics, hemodynamic performance, and efficiency over 4 months of pacing. Methods and Results-After AV nodal ablation, mongrel dogs were randomized to receive 16 weeks of VDD pacing at the RV apex, RV septum,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
91
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 35 publications
7
91
0
Order By: Relevance
“…In contrast, it has been shown that the RV pacing site, which leads to the best LV function, is not predicted by anatomical position or by QRS duration (Peschar et al, 2003). The hemodynamic superiority of LV apex and LV septum pacing may be explained by a relatively physiological sequence of electrical activation when pacing from these sites (Mills et al, 2009;Peschar et al, 2003). Some investigators have proposed the idea of a hemodynamic "sweet spot," where each patient has a particular optimal pacing site (Karpawich & Mital, 1997;Tse et al, 2002;Tse et al, 2009 b).…”
Section: Electric and Mechanic LV Synchronymentioning
confidence: 98%
See 3 more Smart Citations
“…In contrast, it has been shown that the RV pacing site, which leads to the best LV function, is not predicted by anatomical position or by QRS duration (Peschar et al, 2003). The hemodynamic superiority of LV apex and LV septum pacing may be explained by a relatively physiological sequence of electrical activation when pacing from these sites (Mills et al, 2009;Peschar et al, 2003). Some investigators have proposed the idea of a hemodynamic "sweet spot," where each patient has a particular optimal pacing site (Karpawich & Mital, 1997;Tse et al, 2002;Tse et al, 2009 b).…”
Section: Electric and Mechanic LV Synchronymentioning
confidence: 98%
“…In contrast, LV apical and LV septal pacing did not significantly alter these parameters as compared with the values during intrinsic conduction. At 16 weeks, acute intrasubject comparison showed that single-site LV apical and LV septal pacing generally resulted in similar or better contractility, relaxation, and efficiency as compared with acute biventricular pacing (Mills et al, 2009). In the animal study described by Mills et al (Mills et al, 2009), the lead was implanted in the RV midseptum, based solely on position and not optimizing the QRS complex.…”
Section: Electric and Mechanic LV Synchronymentioning
confidence: 99%
See 2 more Smart Citations
“…However, experimental and clinical studies demonstrated that various RV pacing sites did not recruit the His-Purkinje system [2,4]. The majority of LV activation instead occurred via slow and dyssynchronous direct myocardial to myocardial cell conduction and that in terms of mechanical dyssynchrony, hemodynamic and electrical parameters septal pacing was not superior to RVapical pacing [2,4]. A recent cross-sectional multicenter study demonstrated that for pacing in RV, there is no better alternative to apex [5].…”
mentioning
confidence: 99%